Does Tranexamic Acid Reduce the Blood Loss in Various Surgeries? An Umbrella Review of State-of-the-Art Meta-Analysis - Hong, Pan; Liu, Ruikang; Rai, Saroj; Liu, JiaJia; Ding, Yuhong; Li, Jin (Frontiers in Pharmacology, 2022)
Background: Tranexamic acid (TXA) has been applied in various types of surgery for hemostasis purposes. The efficacy and safety of TXA are still controversial in different surgeries. Guidelines for clinical application of TXA are needed. Materials and method: We systematically searched multiple medical databases for meta-analyses examining the efficacy and safety of TXA. Types of surgery included joint replacement surgery, other orthopedic surgeries, cardiac surgery, cerebral surgery, etc. Outcomes were blood loss, blood transfusion, adverse events, re-operation rate, operative time and length of hospital stay, hemoglobin (Hb) level, and coagulation function. Assessing the methodological quality of systematic reviews 2 (AMSTAR 2) and Grading of Recommendations, Assessment, Development and Evaluation (GRADE) were used for quality assessment of the included meta-analyses. Overlapping reviews were evaluated by calculating the corrected covered area (CCA). Result: In all, we identified 47 meta-analyses, of which 44 of them were of “high” quality. A total of 319 outcomes were evaluated, in which 58 outcomes were assessed as “high” quality. TXA demonstrates significant hemostatic effects in various surgeries, with lower rates of blood transfusion and re-operation, shorter operative time and length of stay, and higher Hb levels. Besides, TXA does not increase the risk of death and vascular adverse events, but it is a risk factor for seizure (a neurological event) in cardiac surgery. Conclusion: Our study demonstrates that TXA has a general hemostatic effect with very few adverse events, which indicates TXA is the recommended medication to prevent excessive bleeding and reduce the blood transfusion rate. We also recommend different dosages of TXA for different types of adult surgery. However, we could not recommend a unified dosage for different surgeries due to the heterogeneity of the experimental design. Systematic Review Registration:clinicaltrials.gov/, identifier CRD42021240303